2019
DOI: 10.1002/adhm.201900911
|View full text |Cite
|
Sign up to set email alerts
|

ROS‐Mediated Apoptosis and Anticancer Effect Achieved by Artesunate and Auxiliary Fe(II) Released from Ferriferous Oxide‐Containing Recombinant Apoferritin

Abstract: Reactive oxygen species (ROS)‐mediated apoptosis is considered a crucial therapeutic mechanisms for artesunate (AS). As an Fe(II)‐dependent drug, the anticancer effect of AS is often limited due to insufficient Fe(II) concentration in targeted cells. To overcome this problem, a recombinant apoferritin nanocarrier containing ferriferous oxide (M‐HFn) is constructed to produce auxiliary exogenous Fe(II) when delivering AS to cancer cells. Here, the newly fabricated AS‐loaded M‐HFn nanoparticles (M‐HFn@AS NPs) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…In recent years, artemisinin and its derivatives (e.g., dihydroartemisinin and artesunate) have been recognized as effective antimalarial agents [119]. They also have anticancer and anti-angiogenic properties with cytotoxic effects against several cancer types in vitro and in vivo [120][121][122]. Dihydroartemisinin inhibited the proliferation of HeLa and Caski cells in a dose-and time-dependent manner with IC 50 values of 22.08 and 18.20 µmol/L, respectively.…”
Section: Sesquiterpenoidsmentioning
confidence: 99%
“…In recent years, artemisinin and its derivatives (e.g., dihydroartemisinin and artesunate) have been recognized as effective antimalarial agents [119]. They also have anticancer and anti-angiogenic properties with cytotoxic effects against several cancer types in vitro and in vivo [120][121][122]. Dihydroartemisinin inhibited the proliferation of HeLa and Caski cells in a dose-and time-dependent manner with IC 50 values of 22.08 and 18.20 µmol/L, respectively.…”
Section: Sesquiterpenoidsmentioning
confidence: 99%
“…Direct conjugation of ARTs to transferrin may lead to some drawbacks such as limited loading efficiency and potential suppressive effect to the intrinsic biological functions of transferrin. To overcome the drawbacks, some much advanced nanosystems have been presented (Zhang et al, 2015a,b;Ji et al, 2019;Luo et al, 2019). For example, in a recent study, Xing's group reported a system for pH-triggered cancer chemotherapy by coating graphene oxide (GO) with both transferrin and DHA, where transferrin served as not only a cancer cell-targeting ligand but also an iron carrier (Liu et al, 2015).…”
Section: Iron-containing Soft Matters For Arts Delivery and Activationmentioning
confidence: 99%
“…ROS can function as an important signaling molecule, mediating a myriad of bioactivities, on the other hand, ROS could interact with pivotal cellular targets, including lipid, protein and DNA, leading to serious damage to cellular homeostasis [21]. Various researches demonstrated that ROS could facilitate the anti-neoplastic effect of numerous chemicals, including sodium butyrate [22], artesunate [23], ginsenoside, and so on [24]. Nevertheless, the way TQ regulates the level of intracellular ROS varies among different tissue and cell types [13], and whether TQ can exert its anti-cancer effect via regulating the level of ROS is still unknown.…”
Section: Introductionmentioning
confidence: 99%